Humanized mouse models to study pathophysiology and treatment of HIV infection. Issue 2 (March 2018) - Masse-Ranson, Guillemette; Mouquet, Hugo; Di Santo, James P.
Abstract : Purpose of review: Immunodeficient mice that lack all lymphocyte subsets and have phagocytic cells that are tolerant of human cells can be stably xenografted with human hematopoietic stem cell as well as other human tissues (fetal liver and thymus) creating 'human immune system' (HIS) mice. HIS mice develop all major human lymphocyte classes (B, T, natural killer, and innate lymphoid cell) and their specialized subsets as well as a variety of myeloid cells (dendritic cell, monocytes, and macrophages) thereby providing a small animal model in which to interrogate human immune responses to infection. Recent findings: HIS mouse models have been successfully used to study several aspects of HIV-1 biology, including viral life cycle (entry, restriction, replication, and spread) as well as virus-induced immunopathology (CD4 + T-cell depletion, immune activation, and mucosal inflammation). Recent work has shown that HIV reservoirs can be established in HIV-infected HIS mice after treatment with combinations of antiretroviral drugs thereby providing a model to test new approaches to eliminate latently infected cells. Summary: HIS mice provide cost-effective preclinical platform to assess combination immunotherapies that can target HIV reservoirs. Therapeutic strategies validated in HIS mice should be considered in designing the roadmap toward HIV 'cure'.